Experimentation of NHT And TPS Learning Model Using CTL Approach Towards Mathematics Learning Outcomes Viewed from Student Learning Styles - Siti Rahayu; Rahman Cahyadi (International Journal of Trends in Mathematics Education Research, 2019)
This study aims to find out (1) which NHT cooperative learning model with the CTL approach provides better learning outcomes than the TPS learning model with the CTL approach, (2) which ones provide better learning outcomes for each learning style, (3) in each model with which learning approach provides better learning outcomes in each learning style, (4) in each learning style, which provides better learning outcomes for each model with a learning approach. This study is a quasi-experimental research. The population in this study were all eighth grade students of Sukoharjo Middle School 2 with a sampling technique using ramdom sampling clusters. The data analysis technique uses two-way variance analysis with cells not the same as the normality test prerequisite test and data homogeneity test. The results of this study are (1) The NHT learning model with the CTL approach has better learning outcomes than the TPS learning model with the CTL approach, (2) Students with learning styles on the kinesthetic type provide higher learning outcomes than students with learning styles of the type audio, students' mathematical learning outcomes with learning styles on kinesthetic types as well as students with learning styles in the visual type and student mathematics learning outcomes with learning styles in the visual type as well as students with learning styles on the audio type, (3) for each learning model, consistent with the results of the learning style type, (4) for each  learning style type , it applies consistently to the results of the learning model.